Optimization of LDS blends of Kb:C7 for applications in the P3HT:PC61BM organic photovoltaic device - Pardo Perdomo, Andres David (2024)
Dissertação (Mestrado em Física) - Universidade Estadual de Londrina, Centro de Ciências Exatas, Programa de Pós-Graduação em Física